The influence of intensity and effectiveness of chatgpt use on critical thinking skills of students at the sekolah tinggi ilmu ekonomi YAPAN - Frudensius Berto Umbur; Arif Hidayat (Jurnal Mantik, 2026)
Advances in Artificial Intelligence (AI) technology, particularly ChatGPT developed by OpenAI, have brought changes to various aspects of higher education, including student learning processes. Currently, ChatGPT is widely used as a means to obtain information, assist in completing academic assignments, and support understanding of lecture material. On the other hand, the high level of use of this technology has given rise to various views regarding its impact on students' critical thinking skills. Therefore, this study was conducted to determine the effect of the intensity of ChatGPT use and its effectiveness on the critical thinking skills of STIE YAPAN students. The study used a quantitative approach with a survey method by distributing questionnaires to 193 students selected using a purposive sampling technique. The data obtained were analyzed using multiple linear regression methods with the help of SPSS software. The results showed that the intensity of ChatGPT use did not have a significant effect on students' critical thinking skills, as indicated by a significance value of 0.163 > 0.05. Conversely, the effectiveness of ChatGPT use was proven to have a positive and significant effect on students' critical thinking skills with a significance value of 0.001 < 0.05. In addition, the intensity and effectiveness of ChatGPT use together have a significant effect on students' critical thinking skills, as indicated by a significance value of 0.004 < 0.05